Abū al-Rayḥān al-Bīrūnī and Famous poets and writers in persian literature - nasrin Fallah (تاریخ ادبیات, 2018)
Abū al-Rayḥān al-Bīrūnī, the great Iranian Scientist, has writed many books in various sciences that unfortunately only afew number of his works has remainded. His remainded books has proven his authority in all contemporary sciences. according to this, Famous poets and writers in persian literature, must reflect much various aspects of his scientific personality.This article in analytical- descriptive method on the bases of library References, has Provided data about the manner of reflection of al-Bīrūnī’s features in the most famous works of persian literature, including poem and Prose, especially in the fourth and fifth centuries and then with analytical attitude has evaluated data. The results has shown limited and one-dimentional reflection of this great character or literary history reticence about him which is analyzed Compared to presence of another Scientific characters specificly Greek masters.